Solvable groups derived from fuzzy hypergroups - E. Mohammadzadeh; T. Nozari (Ratio Mathematica, 2015)
In this paper we introduce the smallest equivalence relation ξ ∗ on a finite fuzzy hypergroup S such that the quotient group S/ξ ∗ , the set of all equivalence classes, is a solvable group. The characterization of solvable groups via strongly regular relation is investigated and several results on the topic are presented.